2019
DOI: 10.12788/jhm.3151
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Modeling and Aggregate‐Weighted Scoring Systems in Prediction of Mortality and ICU Transfer: A Systematic Review

Abstract: BACKGROUND:The clinical deterioration of patients in general hospital wards is an important safety issue. Aggregate-weighted early warning systems (EWSs) may not detect risk until patients present with acute decline. PURPOSE:We aimed to compare the prognostic test accuracy and clinical workloads generated by EWSs using statistical modeling (multivariable regression or machine learning) versus aggregate-weighted tools.DATA SOURCES: We searched PubMed and CINAHL using terms that described clinical deterioration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 56 publications
2
47
1
2
Order By: Relevance
“…Without confirmation of acceptable discrimination and calibration, the predictive accuracy of a model cannot be stated firmly [8]. Early warning scores developed using statistical analysis of routinely collected data representative of clinical practice appear to provide both improved discrimination and calibration, with potential for better and more efficient care than is possible [9] using consensus-based scores, such as NEWS-2.…”
Section: Validationmentioning
confidence: 99%
“…Without confirmation of acceptable discrimination and calibration, the predictive accuracy of a model cannot be stated firmly [8]. Early warning scores developed using statistical analysis of routinely collected data representative of clinical practice appear to provide both improved discrimination and calibration, with potential for better and more efficient care than is possible [9] using consensus-based scores, such as NEWS-2.…”
Section: Validationmentioning
confidence: 99%
“…Because the PPV is a function of the disease prevalence, the PPV of the second composite outcome (a + e + f) was even lower. (Linnen et al, 2019). Typically, studies reporting a comparison between an externally developed EWS and an in-house derived score report higher c-statistics in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…The AUROCs calculated for the different outcomes in this study varied significantly (range 0.716–0.885). Studies comparing the performance of different EWSs yielded diverse results (Linnen et al., 2019). Typically, studies reporting a comparison between an externally developed EWS and an in‐house derived score report higher c‐statistics in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…There were 135 papers duplicated between these two categories. Two systematic reviews were identified [18,19]. Given the narrative nature of this review, the final cohort of papers was hand-picked to provide the reader with the best general overview of the topic and was not meant to be comprehensive.…”
Section: Methods Of Literature Selectionmentioning
confidence: 99%